Pengaruh Suhu Karbonisasi Terhadap Kapasitas Adsorpsi Karbon Aktif Tempurung Kelapa Dalam Penyimpanan Biogas - Ersan, Abed Nego; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract The global energy crisis has encouraged the development of renewable energy sources. Biogas as a renewable energy source has great potential but is limited by storage problems. This study aims to improve the efficiency of biogas storage by optimising the production process of coconut shell activated carbon. By varying the carbonisation temperature of 425°C, 525°C, 625°C, this study analysed the effect of these variables on the adsorption capacity of activated carbon. The results showed that the carbonisation temperature of 625°C produced activated carbon with the best performance in biogas storage capacity. In fact, the activated carbon with the highest carbonisation temperature variation not only has more biogas storage capacity, but is also able to produce a greater amount of usable biogas compared to the activated carbon produced at lower carbonisation temperatures. Thus, higher carbonisation temperatures can significantly increase the mass of biogas storage and the use of coconut shell activated carbon can increase the effectiveness of biogas storage compared to storage without the use of activated carbon as an adsorben. Keywords: Biogas, Activated carbon, Coconut shell, Adsorbed Natural Gas (ANG), Microwave activation.